Pertanggungjawaban Pidana terhadap Aktivitas Pertambangan Tanpa Izin yang Merusak Infrastruktur Fisik Desa : (Studi di Desa Sebulu Modern Kecamatan Sebulu Kabupaten Kutai Kartanegara) - Adi Budiman; Haris Retno Susmiyati; Orin Gusta (Pemuliaan Keadilan, 2025)
Illegal mining activities in Sebulu District have become a serious issue as they not only violate the law but also cause significant damage to public infrastructure such as village roads, bridges, and drainage systems, which are deteriorating due to heavy trucks transporting mining materials. Although Article 158 of Law Number 3 of 2020 concerning Mineral and Coal Mining stipulates strict sanctions, law enforcement remains weak. The main contributing factors are local community involvement, inadequate supervision by authorities, and social legitimacy that perceives mining as a normal activity. This study aims to analyze criminal liability for illegal mining offenders and to identify its social and environmental impacts in Sebulu District. The research applies a socio-legal approach that combines normative and empirical methods. The normative approach examines applicable legal provisions, while the empirical approach includes field observations, interviews with local officials and residents, and documentation of relevant regulations and events. The findings indicate that the most severe impacts are the deterioration of village roads and bridges and environmental degradation, such as changes in water color in nearby drainage channels. These conditions cause public concern and disrupt daily life. Weak law enforcement allows illegal mining to persist. Therefore, synergy among law enforcers, local government, and communities is needed to strengthen regulation enforcement and develop sustainable economic alternatives.